PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V PADA PEMBELAJARAN MATEMATIKA MELALUI MODEL INKUIRI DI SEKOLAH DASAR - Degita, Prissillia; Firman, Firman; Efendi, Jon (Jurnal Basicedu, 2019)
This observation is low thingking ability of mathematic students learning in the five class SDN 06 AnakanPesisir Selatan. The direction of this observation describes the description of increasing ability thingking ability of mathematic students in the five class SDN 06 Anakan Pesisir Selatan by using Inkuiri model. The kind of this observation studies observation action. This observation is done in two methods. The data of students in class fiveSDN 06 Anakan Pesisir Selatan is now 11 students. The instrument that is used forthe activities of teacher and thingking ability of student test. Based out the analisys of ability thingking of students percentage of student by him self increase the ability. First 63,33% increase to 73,66%. From these data that is gotten, we can conclude the ability students of mathematic in class fiveSDN 06 Anakan Pesisir Selatan. After using Inkuiri model. The use of Inkuiri model, can be used for studying is more interesting in order to get the maximum result.